1996
DOI: 10.3186/jjphytopath.62.125
|View full text |Cite
|
Sign up to set email alerts
|

Infection Sites of Pseudomonas cichorii into Head Leaf of Lettuce.

Abstract: Sections of middle head leaf of lettuce were stained with fluorescein isothiocyanate-conjug antibody against Pseudomonas cichorii, a causal agent of bacterial rot of lettuce, and were observe under a fluorescent microscope. Fluorescent antibody-labeled P. cichorii cells were observed in stomat of the sections, which did not contain browing symptom of the disease. Special fluorescent specks deriv from P. cichorii were most frequently observed in guard cells and intercellular spaces of substoma cavities. Browing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Numerous lesions enlarged and coalesced, causing moist, greenish or yellowish to black areas, but no soft rot was observed on the infected plants in advanced stages of the disease. These symptoms were consistent with those of bacterial rot described by Hikichi et al . (1996).…”
supporting
confidence: 92%
“…Numerous lesions enlarged and coalesced, causing moist, greenish or yellowish to black areas, but no soft rot was observed on the infected plants in advanced stages of the disease. These symptoms were consistent with those of bacterial rot described by Hikichi et al . (1996).…”
supporting
confidence: 92%
“…[ 6 ] demonstrated that P. cichorii strains acquired the hrp genes through horizontal transfer from a common ancestor with the S-PAI of P. viridiflava and implicated the hrp in its virulence. Symptoms on P. cichorii -infected lettuce leaves are characterized by shiny, dark brown, firm necrotic spots [ 2 , 3 ]. P. cichorii also causes necrotic spots on eggplant distinct from the disease symptoms on lettuce leaves [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas cichorii causes bacterial rot in lettuce, which is characterized by shiny, dark brown, firm necrotic spots on leaves underneath the second or the third outermost head-leaves [ 1 , 2 , 3 ]. P. cichorii reportedly causes midrib rot of greenhouse-grown butterhead lettuce [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…1977). The pathogen enters lettuce head leaves, in contact with outer leaves, through stomata, multiplies in intercellular spaces of epidermis and mesophyll and moves into the vascular bundle (Hikichi et al. 1996a,b, 1998).…”
Section: Introductionmentioning
confidence: 99%